Relationship Between Food Consumption Patterns, Stress Levels and Drug Use in Recurrence of Dyspepsia at Widya Dharma Husada Clinic - Arief, Ilham; Fahriati, Andriyani Rahmah; Sari, Sulfia (Yayasan Gema Bina Nusantara, 2025)
Dyspepsia is a common digestive disorder characterized by symptoms such as nausea, bloating, and epigastric pain. This study aims to analyze the relationship between dietary patterns, stress levels, and medication use on the recurrence of dyspepsia among patients at Widya Dharma Husada Clinic, Tangerang. A quantitative approach with a cross-sectional design was employed. The sample consisted of 73 respondents selected from a population of 90 dyspepsia patients. Data were collected using a closed-ended questionnaire and observation sheet, and analyzed using correlation tests with SPSS software. The results showed that most respondents were aged 17–19 years (53.4%), female (86.3%), had poor dietary patterns (69.9%), experienced mild stress levels (53.4%), and used antacid medication (39.7%). The majority of respondents did not experience a recurrence of dyspepsia (75.3%). Bivariate analysis indicated a significant relationship between dietary patterns and dyspepsia recurrence (p = 0.001), but no significant relationship was found between stress levels (p = 0.274) or medication use (p = 0.274) and the recurrence of dyspepsia. This study highlights the importance of maintaining healthy eating habits as a preventive measure against dyspepsia recurrence, particularly among university students.